Evidenceon the Fiscal and Macroeconomic Impact of Privatization - Barnett, Steven (IMF Working Papers; Working Paper, 2000)
This paper empirically investigates the relationship between privatization and measures of fiscal and macroeconomic performance. One of the main findings is that privatization proceeds transferred to the budget tend to be saved. Specifically, they are largely used to reduce domestic financing, with little evidence that they are used to finance a larger deficit. However, by construction, this part of the study is restricted to privatization proceeds transferred to the budget, leaving open the question of what happens to those proceeds not transferred to the budget. The other main finding is that total privatization (as opposed to just the proceeds transferred to the budget) is correlated with an improvement in macroeconomic performance as manifested in higher real GDP growth and lower unemployment. However, this result needs to be interpreted cautiously as the evidence is not sufficient to establish causality.